Plasma membrane damage causes NLRP3 activation and pyroptosis during Mycobacterium tuberculosis infection - Kai S. Beckwith (Nature Portfolio, 2020)
Inflammasome activation is a response to bacterial infection but can cause damage and spread infection. Here, the authors use live single-cell imaging to show two mechanisms by which M. tuberculosis causes damage to human macrophage cell plasma membranes, resulting in activation of the NLRP3 inflammasome, pyroptosis and release of infectious particles.